Distribution and Speciation of Dissolved Iron in Jiaozhou Bay (Yellow Sea, China) - Su, Han; Yang, Rujun; Pižeta, Ivanka; Omanović, Dario; Wang, Shirong; Li, Yan (Frontiers in Marine Science, 2016)
The distribution of total dissolved iron (DFe) and its chemical speciation were studied in vertical profiles of the shallow and semi-closed Jiaozhou Bay (JZB, China) during two contrasting periods: summer (July 19th, 2011) and spring (May 10th, 2012). Samples collected from the surface, middle and bottom layers were analyzed by competitive ligand exchange-adsorptive cathodic stripping voltammetry (CLE-aCSV). The mean DFe concentration during the summer period (median 18.8 nM; average 20.7 nM) was higher than in the spring period (median 12.4 nM; average 16.9 nM), whereas the spatio-temporal variation in spring was larger than in summer. The DFe values showed distinct regional and seasonal differences, ranging from 5.6-107nM in spring period and 13.4-43.4 nM in summer period. In spring, the highest DFe values were observed in the eastern coastal region, especially near an industrial area (up to 107nM), whereas the DFe distribution in summer was relatively even. Due to a tide influence, the vertical variations in the DFe and Lt in both seasons were not significant. On average, the Lt concentration (one class of ligand was estimated in all samples), was higher in spring (35.2±23.4 nM) than in summer (31.1±10.3 nM). A statistically significant correlation was found between Lt and DFe concentrations, it was higher for the summer period than for the spring period. The conditional stability constants (logK') of organic complexes with iron were weaker in spring (11.7±0.3) than in summer (12.3±0.3). The concentrations of Lt were higher in comparison to DFe in all samples: the average [Lt]/[DFe] ratio in the spring and summer samples was 2.4 and 1.5, respectively. Speciation calculations showed that the DFe in the JZB existed predominantly (over 99.99%) in the form of strong organic complexes in both seasons.